Urinary elimination of styrene in experimental and occupational exposure. - Pezzagno, G.; Ghittori, S.; Imbriani, M.; Capodaglio, E. (Scandinavian Journal of Work, Environment & Health, 1985)
Twenty human volunteers were exposed to styrene vapor at 273-1 654 mumol/m3 (28.4-172.3 mg/m3) for a period of 1 to 3 h at rest (15 cases) and during light physical exercise (5 cases). Subsequently 51 workers occupationally exposed to styrene were studied during a workweek (median value 1 138 mumol/m3, geometric standard deviation 2.23). As expected, the relative uptake averaged about 65%, and the ratio of the alveolar concentration to the time-weighted average of the environmental concentration averaged about 0.15. Both in the experimentally exposed subjects and in the occupationally exposed workers the urinary styrene concentration showed a linear relationship to the corresponding environmental time-weighted average concentration. The correlation coefficients of the regression lines ranged between 0.88 (occupationally exposed group) and more than 0.93 (experimentally exposed groups). The regression coefficients were closely linked to the amount of styrene taken up and to the exposure times. The findings show that the urinary styrene concentration can be used as an appropriate biological exposure indicator whose meaning differs from that of other suggested indices. As an example, in occupationally exposed subjects performing moderate work the urinary styrene concentration corresponding to the time-weighted average of the threshold limit value is 815 nmol/l, and the 95% lower confidence limit (biological threshold) is 740 nmol/l.